Description of a new species of the genus Mongolotettix Rehn, 1928 (Orthoptera: Acrididae) from Fujian, China - Chen, Shen-Zhi; Shi, Jian-Ping; Dai, Li (Zootaxa, 2018)
A new species of the genus Mongolotettix Rehn, 1928 from Fujian, China is described in this paper. The new species Mongolotettix.fujianensis sp. nov. is similar to M. wulingyuanensis Shi, Liu et Li, 2016, but differs from the latter by maximum width of cubital area 1.4 times maximum width of medial area in tegmina of male; body small, length of body ♂ 21.5. mm, ♀ 30.6 mm; vertical diameter eye 1.3 times horizontal diameter in male; hind femur of male with 103 stridulatory pegs on inner side and epiphallus with indistinct projection on inner side of lateral plates. Type specimens are deposited in the Shanghai Entomological Museum, Chinese Academy of Sciences, Shanghai, 200032, China.